2009
DOI: 10.1097/ncq.0b013e3181a4699a
|View full text |Cite
|
Sign up to set email alerts
|

Providing a Healthy Work Environment for Nurses

Abstract: Differences in registered nurses' (RNs) perceptions of their work environment were measured with the Insel and Moos' Work Environment Scale to identify factors in the work environment that may influence retention. Statistically significant differences for perceptions of supervisor support and innovation were found between those RNs who left their unit or hospital during a 24-month period and those who stayed. Implementing strategies to promote retention of RNs to ensure safe, quality patient care is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 20 publications
2
63
0
3
Order By: Relevance
“…Two factors are calculated to create a work stress index (α = .80) comprised of the subscales of work pressure, control (by management), clarity (reversed), autonomy (reversed), and a work resources inventory (α = .83) comprised of the subscales of involvement, cohesion, and supervisor support. Previous research with WES is also sensitive to real-world employment outcomes (Cohen, Stuenkel, & Nguyen 2009; Westerman & Yamamura, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Two factors are calculated to create a work stress index (α = .80) comprised of the subscales of work pressure, control (by management), clarity (reversed), autonomy (reversed), and a work resources inventory (α = .83) comprised of the subscales of involvement, cohesion, and supervisor support. Previous research with WES is also sensitive to real-world employment outcomes (Cohen, Stuenkel, & Nguyen 2009; Westerman & Yamamura, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…A favorable working environment increases the interception of medication errors in intensive care (9) . The relationship between a positive working environment and the satisfaction and retention of nurses was also demonstrated (10)(11) , as well as the safety of clients (12)(13) . In contrast, when the work environment is not favorable, the lack of satisfaction of nurses, the burnout syndrome, emotional exhaustion and intention to leave the place of work/service are observed (14)(15)(16)(17)(18)(19) .…”
Section: Study Of Adaptation and Validation Of The Practice Environmementioning
confidence: 99%
“…There is an association between effective nursing leadership and the empowerment of nurses in the practice environment allied with higher job satisfaction (Laschinger, Finegan, Shamian, & Wilk, 2004). Also, one study shows that registered nurses who reported greater levels of support from their supervisors were less expected to leave their position than were registered nurses who reported lesser levels (Cohen, Stuenkel & Nguyen, 2009). The importance of leadership concluded the leaders' skills to inspiration other aspects of the work environment, such as staffing & resources, skill mix, and improved involvement in the organization (Leiter &Laschinger, 2006).…”
Section: Nurse Manager Ability Leadership and Support Of Nursesmentioning
confidence: 99%